Implementasi Simple Network Management Protocol (SNMP) Untuk Melakukan Monitoring Dan Manajemen Jaringan Pada SMK N 5 Kota Bengkulu - Januar Syah Putra; Khairil Khairil; Deri Lianda (UNIVED Press, 2025)
The purpose of this research is to implement Simple Network Management Protocol (SNMP) to monitor and manage the network at SMK N 5 Bengkulu City to, especially the computer network of SMK N 5 Bengkulu City, so that with the implementation of Simple Network Management Protocol (SNMP) to monitor and manage the network at SMK N 5 Bengkulu City it becomes better, useful and can be used to support teaching and learning activities. Monitoring the computer network of SMK N 5 Bengkulu City uses Nagios software and to perform network management using Squid Proxy. In monitoring the nagios network, it can display how many devices are connected (hidip) and devices that are not connected (dead), while the squid proxy can manage websites that cannot be accessed via the network and can manage the amount of bandwidth on each device. In managing websites that cannot be accessed via the network, the website address must be entered manually into the squid proxy in the facilities provided, namely access control.